The role of the supervisor in the supervisory process - Lessing, AC (South African Journal of Higher Education, 2011)
Postgraduate supervision does not only require academic and research skills from the supervisors – they may also assume a variety of roles to support the postgraduate student from novice to experienced researcher. The role of supervisors in the supervisory process, as well as the views of a purposeful selection of lecturers on the role is the focus of this article. The role of supervisors was determined from the literature and a questionnaire was administered to lecturers in the School of Education (University of South Africa) to investigate their views. Clear views of the role of the supervisor emerged from the literature study, but the lecturers who participated saw very few of these identified tasks as part of their responsibility. To increase the throughput of master and doctoral students, lecturers may have to make a mind shift with regard to their role in the supervisory process.